3D Printing of Metal/Metal Oxide Incorporated Thermoplastic Nanocomposites With Antimicrobial Properties - Abdullah, Turdimuhammad; Qurban, Rayyan O.; Bolarinwa, Sherifdeen O.; Mirza, Ahmed A.; Pasovic, Mirza; Memic, Adnan (Frontiers in Bioengineering and Biotechnology, 2020)
Three-dimensional (3D) printing has had steady increase in popularity for direct manufacturing, where complex geometric items can be produced without aid of templating tools and manufacturing waste can be remarkably reduced. While customized medical devices and daily life items can be made by 3D printing of thermoplastics, microbial contamination has been a serious issue during their usage. A very clever approaches to overcome this challenge is to incorporate antimicrobial metal or metal oxide (M/MO) nanoparticles within the thermoplastics during 3D printing. Many M/MO nanoparticles can protect infection from wide ranges of microorganism, including antibiotic-resistant bacteria, as they show various antimicrobial mechanism. Additionally, they can be easily printed with thermoplastic without loosing their integrity and functionality. In this overview, we summarize recent advancements and discuss future trends related to the development of 3D printed antimicrobial thermoplastic nanocomposites by addition M/MO nanoparticles.